Development of an innovative in vivo model of PJI treated with DAIR - Poilvache, Hervé; Van Bambeke, Françoise; Cornu, Olivier (Frontiers in Medicine, 2022)
Introduction: Periprosthetic joint infections (PJI) are catastrophic complications of joint replacement. Debridement, implant retention, and antibiotic therapy (DAIR) is the usual strategy in acute infections but fails in 45% of MRSA infections. We describe the development of a model of infected arthroplasty in rabbits, treated with debridement and a course of vancomycin with clinically relevant dosage. Methods: 15 rabbits were assigned to 3 groups: vancomycin pharmacokinetics (A), infection (B), and DAIR (C). All groups received a tibial arthroplasty using a Ti-6Al-4V implant. Groups B, and C were infected per-operatively with a 5.5 log10 MRSA inoculum. After one week, groups C infected knees were surgically debrided. Groups A, and C received one week of vancomycin. Pharmacokinetic profiles were obtained in group A following 1st and 5th injections. Animals were euthanized two weeks after the arthroplasty. Implants and tissue samples were processed for bacterial counts and histology. Results: Average vancomycin AUC0-12 were 213.0mg*h/L (1st injection) and 207.8mg*h/L (5th injection), reaching clinical targets. All inoculated animals were infected. CFUs were reproducible in groups B. A sharp decrease in CFU was observed in groups C. Serum markers and leukocytes counts increased significantly in infected groups. Conclusion: We developed a reproducible rabbit model of PJI treated with DAIR, using vancomycin at clinically relevant concentrations.